1979
DOI: 10.1007/bf00344840
|View full text |Cite
|
Sign up to set email alerts
|

Competition between freshwater fish and goldeneyes Bucephala clangula (L.) for common prey

Abstract: Results of a descriptive field study showed that goldeneyes preferred lakes without fish to those with fish. Field experiments were carried out in order to investigate whether or not this preference could be ascribed to a higher food supply in the lakes devoid of fish, as goldeneyes and some freshwater fish (perch and roach in the studied lakes) to some extent feed on the same kinds of prey. Changes in the abundance of prey common to fish and goldeneyes and the use by goldeneyes of lakes after experimentally c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 9 publications
2
64
0
1
Order By: Relevance
“…Furthermore, Goldeneyes typically feed on a wide range of invertebrates in the central parts of lakes, whereas Mallard and Teal tend to feed at the edge of lakes and Tufted Ducks mainly feed on molluscs. Goldeneyes are found to occur in higher numbers at lakes with low fish densities, possibly as a result of competition for invertebrate prey (Eriksson 1979), but do not appear to affect fish stocks per se.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Goldeneyes typically feed on a wide range of invertebrates in the central parts of lakes, whereas Mallard and Teal tend to feed at the edge of lakes and Tufted Ducks mainly feed on molluscs. Goldeneyes are found to occur in higher numbers at lakes with low fish densities, possibly as a result of competition for invertebrate prey (Eriksson 1979), but do not appear to affect fish stocks per se.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the high density of diving ducks in 2003 (Table 2) is related to this recurrence of attractive macro-invertebrates in the lake. This is supported by experimental studies on competition between fish and ducks in small lakes in Sweden (Eriksson 1979) and England (Giles 1994). In both cases, abundances of macroinvertebrates increased when fish were removed, and this had positive effects on the use of lakes by diving ducks.…”
Section: Discussionmentioning
confidence: 72%
“…Some coarse fish species eat similar invertebrates to Mallard (Eriksson 1979, Pehrsson 1984 and Goldeneye Bucephala clangula ducklings (McAllister Eadie & Keast 1982) and fish removal can result in an increase of certain benthic macroinvertebrates such as some crustacea and members of the family Chironomidae (Eriksson 1979, Gilinsky 1984, Morin 1984.…”
Section: Discussionmentioning
confidence: 99%
“…Eriksson (1979) showed that broods preferred lakes without fish and that their use of an experimental lake increased after fish were removed. Pehrsson (1 979) showed that the highest rate of food intake in Mallard ducklings occurred on lakes where fish had been removed, and further, by experiment Pehrsson (1984) showed that ducklings obtained more food in lakes where fish had been removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation